Management Control System Design and Innovation: A Systematic Literature Review - Wijayanti, Dian; Cahyadi, Rino Tam (Jurnal Economia, 2024)
AbstractThe purpose of this study is to examine through a systematic review the management accounting research that focuses on the role of management control systems (MCS) in enhancing innovation within organizations. For that purpose, a total of 19 articles from publications spanning from 2000 to 2022 were selected using the keywords of management control system and innovation. The findings indicate that the Levers of Control (LoC) is the most widely studied topic. The next popular topic being examined is formal and informal control mechanisms. The aspect of innovation in that literature mainly focuses on product innovation, management and organizational innovation, and environmental innovation and sustainability. Future research can explore more the role of the MCS in the combined mechanism of LoC to encourage innovation. This paper contributes to the MCS literature by examining the suitable mechanisms affecting the success of innovation in a rapidly changing environment.  Keywords:Management Control System, Innovation, Review Literature, Levers Of Control, New Product Development